Peran Mahkamah Konstitusi dalam Perlindungan Hak Pilih dalam Negara Hukum Demokratis - Agusniwan Etra (Constitutional Court of the Republic of Indonesia, Indonesia, 2022)
The involvement of ex-convicts in political contests sparked a discourse on human rights and their protection by the Constitutional Court. This paper will answer constitutional dynamics of these rules through the decisions of the Constitutional Court. This research uses normative-legal method. The result shows that since the beginning, the regulation has been declared conditionally unconstitutional, but the requirements and implementation of it have developed in subsequent decisions. The Court has determined four constitutional requirements cumulatively in the form of not being revoked by a court decision; limited to a period of 5 (five) years; admits being a former convict openly and honestly; and not as a recidivist. The Court changed its stance that the requirement applies alternatively if there is an honest and open acknowledgment as an ex-convict, then other conditions are no longer needed. However, in its final decision, the Court restored the validity of the previous four cumulative conditions.